2014
DOI: 10.1371/journal.pone.0108713
|View full text |Cite|
|
Sign up to set email alerts
|

Isolation, Cytotoxicity Evaluation and HPLC-Quantification of the Chemical Constituents from Prangos pabularia

Abstract: Phytochemical analysis of the dichloromethane:methanol (1∶1) extract of root parts of Prangos pabularia led to the isolation of twelve cytotoxic constituents, viz., 6-hydroxycoumarin (1), 7-hydroxycoumarin (2), heraclenol-glycoside (3), xanthotoxol (4), heraclenol (5), oxypeucedanin hydrate (6), 8-((3,3-dimethyloxiran-2-yl)methyl)-7-methoxy-2H-chromen-2-one (7), oxypeucedanin hydrate monoacetate (8), xanthotoxin (9), 4-((2-hydroxy-3-methylbut-3-en-1-yl)oxy)-7H-furo[3,2-g]chromen-7-one (10), imperatorin (11) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 27 publications
2
23
0
Order By: Relevance
“…This hypothesis was confirmed by the fact that when umbelliprenin was encapsulated in nanoliposomes its antiproliferative effect against 4T1 cells increased by five folds 50 . Also osthol (12) showed only a moderate cytotoxicity with an IC 50 of 98 lM but, as reported in previous works 54,55 , its cytotoxicity greatly depends on the cancer cell line.…”
Section: Cytotoxicity Of Compounds 5 9-12 and 15 Towards Cancer Cellssupporting
confidence: 72%
“…This hypothesis was confirmed by the fact that when umbelliprenin was encapsulated in nanoliposomes its antiproliferative effect against 4T1 cells increased by five folds 50 . Also osthol (12) showed only a moderate cytotoxicity with an IC 50 of 98 lM but, as reported in previous works 54,55 , its cytotoxicity greatly depends on the cancer cell line.…”
Section: Cytotoxicity Of Compounds 5 9-12 and 15 Towards Cancer Cellssupporting
confidence: 72%
“…Interestingly, the species are not evenly distributed. In fact, several families contain a strikingly large number of members compared with other plant families [50].…”
Section: Discussionmentioning
confidence: 99%
“…These diterpene molecules are considered as the first representatives of this family to be described from the plant kingdom [25]. The current research programme was undertaken as part of our on-going research programme based on bioprospection of natural products [26][27][28][29][30][31][32]. Thorough review of literature revealed no reports of phytochemistry on S. sclarea of Kashmir origin.…”
Section: Advances In Biomedicine and Pharmacy (An International Journmentioning
confidence: 99%